Metabolic effects of milk protein intake strongly depend on pre-existing metabolic and exercise status - Melnik, Bodo C (BioMed Central, 2013)
Milk protein intake has recently been suggested to improve metabolic health. This Perspective provides evidence that metabolic effects of milk protein intake have to be regarded in the context of the individual’s pre-existing metabolic and exercise status. Milk proteins provide abundant branched-chain amino acids (BCAAs) and glutamine. Plasma BCAAs and glutamine are increased in obesity and insulin resistance, but decrease after gastric bypass surgery resulting in weight loss and improved insulin sensitivity. Milk protein consumption results in postprandial hyperinsulinemia in obese subjects, increases body weight of overweight adolescents and may thus deteriorate pre-existing metabolic disturbances of obese, insulin resistant individuals.